A standardized enzyme-linked immunosorbent assay (ELISA) for the detection of Infectious bronchitis virus antibodies in serum and tracheobronchial lavage samples of chickens - Di Giacomo, Sebastián; Gerez Miranda, Rocio Del Carmen; Olivera, Valeria Soledad; Asenzo, Gustavo Daniel; Jaton, Juan Marcelo; Vagnozzi, Ariel Eduardo (American Association of Avian Pathologists, 2025)
Infectious bronchitis (IB) is a major viral disease that causes substantial economic losses in the global poultry industry. Despite the implementation of extensive vaccination programs, it remains a persistent threat. Monitoring the antibody response against infectious bronchitis virus (IBV) is essential for studies focused on vaccine development, as well as for evaluating the effectiveness and proper administration of vaccines in poultry flocks. In this study we developed and optimized an indirect enzyme-linked immunosorbent assay (IB-ELISA) for the detection of IBV-specific antibodies. The use of purified virus, obtained through sucrose density gradient centrifugation, was critical for minimizing nonspecific background reactivity. A panel of antisera and tracheobronchial lavage samples from IBV-infected and inactivated-vaccine-immunized chickens was tested. The IB-ELISA demonstrated 100% sensitivity and specificity when compared with a commercial IBV ELISA kit used as the gold standard. The assay reliably detected IBV-specific IgG antibodies in both serum and tracheobronchial lavage samples, with positive responses observed as early as 7 days postinfection and 21 days postvaccination, respectively. Although the IB-ELISA could not differentiate between IBV serotypes because of cross-reactivity, it effectively identified antibodies against multiple strains. These findings indicate that the IB-ELISA is a valuable tool for assessing the effectiveness of vaccination programs and for studies requiring the evaluation of both mucosal and systemic IgG responses, including those involving experimental vaccines.